The Need For Biotechnology PjBL-STEM Based Learning Programs Associated with Local Contexts to Enhance Creative Problem Solving and Entrepreneurial Skills: Teacher and Student Perspectives - Dartia Utari; Abdurrahman; Dewi Lengkana; Neni Hasnunidah (Jurnal Penelitian Pendidikan IPA, 2024)
This study evaluates the need for biotechnology PjBL-STEM Based Learning programs associated with local contexts to enhance Creative Problem Solving Skills (CPSS) and Entrepreneurial Skills (ES) from the perspectives of students and teachers. Using a mixed-methods approach with a sequential explanatory design, data were collected through questionnaires from 144 science teachers in Lampung Province and in-depth interviews with three teachers and three students. The findings reveal that 66.70% of teachers consider the current learning programs inadequate for developing students' CPSS and ES, while 68.10% believe that a PjBL-STEM program would facilitate a more engaging understanding of biotechnology. Furthermore, 89.60% of teachers agree on the necessity of developing biotechnology PjBL-STEM based learning programs to enhance students' CPSS and ES. The results from the questionnaires and in-depth interviews also revealed that both teachers and students agreed that the use of local context can make learning more relevant for students. Overall, both quantitative and qualitative data indicate a strong support for the implementation of biotechnology PjBL-STEM based learning programs grounded in local contexts to better develop students' CPSS and ES.